Impact of health index and hospitals on dissemination of antibiotic resistance in two sewersheds of the third largest metropolitan region of Brazil - Henrique Alves Santos; Ana Paula Assad de Carvalho; Juliana Calábria de Araújo (Cleaner Water)
Antimicrobial resistance (AMR) stands as a critical threat to global public health. Wastewater-based epidemiology (WBE) provides health data within communities via sewage analysis. This study delved into antibiotic resistance prevalence across two sewersheds in Belo Horizonte, each with distinct health vulnerability indexes (HVI) and number of hospitals. Bacteria resistant (ARB) to amoxicillin, azithromycin, cephalexin, sulfamethoxazole + trimethoprim, meropenem and ARGs (Intl1, sul1, blaTEM, blaKPC) were quantified in sewage from the two sewersheds over the years from 2020 to 2023. Statistical analysis revealed no significant differences in median concentrations of ARBs between sewersheds, except for bacteria resistant to meropenem. ARGs Investigated exhibited similar patterns, with blaKPC showing statistical significant difference. This suggests that hospital density within a sewershed exerts a more pronounced influence on AMR dissemination than HVI. The difference found in meropenem-resistant bacteria, a hospital-prescribed carbapenem, and blaKPC concentrations underscores the impact of hospital antibiotic usage. Thus, the presence and number of hospitals emerges as a pivotal factor in AMR spread, emphasizing the need for specific treatment and management of hospital wastewater to curb antimicrobial resistance.